Hubungan Aktivitas Fisik, Pola Makan, Lama Menstruasi dengan Kejadian Anemia pada Mahasiswa Kebidanan Reguler di Universitas Kader Bangsa Tahun 2021 - Lucia Rafizka Claudia; Ahmad Arif; Helni Anggraini (Universitas Batanghari Jambi, 2023)
Anemia is caused by a lack of iron in the body. Iron deficiency itself can be caused by several things, such as low iron food intake or maybe iron in food is found in a form that is difficult to absorb, normal anemia <12mg / dl.The purpose of this study is to find out the relationship between physical activity, diet, menstrual period at Universitas Kader Bangsa Palembang in 2021. the design of this type of research is surveyanalytical with a Cross Sectional design. This research was conducted in January – February 2022 at the Universitas Kader Bangsa Palembang. The population in this study was all obstetrics students totaling 51 people, a sample was taken of 40 respondents and the total sampling technique. Students who experienced anemia were 27 people (67.5%) and did not experience anemia, namely 13 people (32.5%) And from the chi-square trial, a p value =(0.011 ≤α = 0.05) was obtained, from respondents who had heavy physical activity and anemia, namely 27 people (67.5%) and light physical activity who did not experience anemia, namely 13 people (32.5%), and from the chi-square test, a p value = (0.031 ≤α = 0.05) was obtained, from respondents who experienced an inappropriate diet who experienced anemia, namely 27 people (67.5%) and an appropriate diet who did not experience anemia that is, as many as 13 people (32.5%). And from the Chi-Square test, the P value = (0.013 ≤α = 0.05) was obtained from respondents who had abnormal menstruation for 27 people (67.5%) and normal menstrual periods who did not have anemia as many as 13 (32.5%). Thus there is a meaningful correlation simultaneously and between physical activity or diet and the duration of menstruation with the incidence of anemia. The results of this study are expected to be used as input to improve the quality of regular student health so as to reduce the incidence of anemia at Universitas Kader Bangsa.